The effect of chitosan addition on cellular uptake and cytotoxicity of ursolic acid niosomes - MIATMOKO, ANDANG; HARIAWAN, BERLIAN S.; CAHYANI, DEVY M.; SARI, RETNO; DINARYANTI, ARISTIKA; HENDRIANTO, ERYK (Anais da Academia Brasileira de Ciências, 2021)
This study evaluated the cellular uptake and cytotoxicity of low permeable Ursolic acid (UA) on cancer cells using niosomes composed of span 60 and cholesterol. The results showed that the addition of chitosan increased particle sizes and ζ-potentials. The UA niosomes with chitosan layers had higher cytotoxicity in HeLa cells than without chitosan, however, there was no improvement observed for Huh7it cells. Moreover, chitosan layers improved the cellular uptake, which clathrin-mediated endocytosis may determine the cellular transport of UA niosomes. In conclusion, the addition of chitosan improved cellular uptake and cytotoxicity of UA niosomes in the HeLa cells.